MODERN SYSTEMS FOR QUALITY IMPROVEMENT AND CASTING FOR THE STEEL AND FOUNDRY INDUSTRIES - V. I. Zolotukhin; E. I. Gordeev; A. G. Golovko; D. A. Provotorov (Литьë и металлургия)
Developments of steel-pouring systems of new generation and grogs to them are presented to NPP «Vulcan-TM».